2003
DOI: 10.1101/gr.700503
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Conservation of Regulatory Elements in Vertebrate Hox Gene Clusters

Abstract: Comparisons of DNA sequences among evolutionarily distantly related genomes permit identification of conserved functional regions in noncoding DNA. Hox genes are highly conserved in vertebrates, occur in clusters, and are uninterrupted by other genes. We aligned (PipMaker) the nucleotide sequences of the HoxA clusters of tilapia, pufferfish, striped bass, zebrafish, horn shark, human, and mouse, which are separated by approximately 500 million years of evolution. In support of our approach, several identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 80 publications
10
116
1
3
Order By: Relevance
“…In a recent comparative analysis of the HoxA cluster in human, horned shark and zebrafish (Chiu et al 2002), extensive conservation of non-coding sequence motifs was found between the human and shark sequences, whereas zebrafish sequences exhibited significant loss of conservation. The majority of newly identified regulatory elements for this cluster of genes were identical to known binding sites for regulatory proteins as defined in the transcription factor database, TRANSFAC (http://www.biobase.de; Matys et al 2003), demonstrating the accuracy of this approach (Matys et al 2003;Santini et al 2003).…”
Section: The Contributions Of Marine and Freshwater Organisms To Compmentioning
confidence: 82%
“…In a recent comparative analysis of the HoxA cluster in human, horned shark and zebrafish (Chiu et al 2002), extensive conservation of non-coding sequence motifs was found between the human and shark sequences, whereas zebrafish sequences exhibited significant loss of conservation. The majority of newly identified regulatory elements for this cluster of genes were identical to known binding sites for regulatory proteins as defined in the transcription factor database, TRANSFAC (http://www.biobase.de; Matys et al 2003), demonstrating the accuracy of this approach (Matys et al 2003;Santini et al 2003).…”
Section: The Contributions Of Marine and Freshwater Organisms To Compmentioning
confidence: 82%
“…Extensions of TBA to automatically produce the richer class of blocksets obtained by dropping these requirements remain as future work. We applied TBA to approximately the same sequences from the HoxA region that were studied in Santini et al (2003), four from mammals and four from fish. When the threaded blockset computed by TBA is projected onto tilapia, many noncoding matches with Fugu are apparent, as are a few putatively noncoding matches with mammals (Fig.…”
Section: Threaded Blockset Alignermentioning
confidence: 99%
“…Substantial evidence exists that ohnologs can be maintained for hundreds of millions of years before lineagespecific loss. For example, the recent loss of MSX3, which arose in R2 and was lost only after primate and rodent divergence perhaps 500 million years after the R2 event; the conversion of Hoxa7a to a pseudogene in the tetraodontiform lineage including pufferfish after it diverged from the lineage including striped bass and tilapia (Perciformes), which retain the gene (Snell et al, '99;Santini et al, 2003;Amores et al, 2004); and the loss of Hoxb7a in the lineage of the Japanese pufferfish (Takifugu rubripes) after it diverged from the lineage to which the green spotted pufferfish (Tetraodon nigroviridis) belongs just 5-35 Mya, nearly 300 million years after the R3 duplication event (Santini and Tyler, '99;Amores et al, 2004).…”
Section: A Consequence For Lineage Divergencementioning
confidence: 99%